Dexmedetomidine pretreatment alleviates cerebral ischemia/reperfusion injury by inhibiting neuroinflammation through the JAK2/STAT3 pathway - Liu, Huan; Li, Jianli; Jiang, Li; He, Jinhua; Zhang, Huanhuan; Wang, Keyan (Brazilian journal of medical and biological research, 2022)
Dexmedetomidine (DEX) is known to provide neuroprotection against cerebral ischemia and reperfusion injury (CIRI), but the exact mechanisms remain unclear. This study was conducted to investigate whether DEX pretreatment conferred neuroprotection against CIRI by inhibiting neuroinflammation through the JAK2/STAT3 signaling pathway. Middle cerebral artery occlusion (MCAO) was performed to establish a cerebral ischemia/reperfusion (I/R) model. Specific-pathogen-free male Sprague-Dawley rats were randomly divided into Sham, I/R, DEX, DEX + IL-6, and AG490 (a selective inhibitor of JAK2) groups. The Longa score, TTC staining, and HE staining were used to evaluate brain damage. ELISA was used to exam levels of TNF-[alpha]. Western blotting was used to assess the levels of JAK2, phosphorylated-JAK2 (p-JAK2), STAT3, and phosphorylated-STAT3 (p-STAT3). Our results suggested that both pretreatment with DEX and AG490 decreased the Longa score and cerebral infarct areas following cerebral I/R. After treatment with IL-6, the effects of DEX on abrogating these pathological changes were reduced. HE staining revealed that I/R-induced neuronal pathological changes were attenuated by DEX application, consistent with the AG490 group. However, these effects of DEX were abolished by IL-6. Furthermore, TNF-[alpha] levels were significantly increased in the I/R group, accompanied by an increase in the levels of the p- JAK2 and p-STAT3. DEX and AG490 pretreatment down-regulated the expressions of TNF-[alpha], p-JAK2, and p-STAT3. In contrast, the down-regulation of TNF-[alpha], p-JAK2, and p-STAT3 induced by DEX was reversed by IL-6. Collectively, our results indicated that DEX pretreatment conferred neuroprotection against CIRI by inhibiting neuroinflammation via negatively regulating the JAK2/STAT3 signaling pathway. Key words: Dexmedetomidine; Cerebral ischemia/reperfusion injury; Neuroprotection; JAK2/STAT3 signaling pathway; Inflammation